Beyond the Wall - Dagh, Danish; Hayat, Noroz; Weldon, Susan; Jahani, Carina (Orientalia Suecana, 2025)
We are pleased to present the English translation of a short story written in Balochi, Beyond the Wall, together with an introduction to the life and work of the author, Danish Dagh. We also include the Balochi text of the story in Latin and Arabic script. It is our hope that this story will challenge its readers to refrain from judging other people and to begin questioning things they may have believed without ever considering whether they are right or wrong, to start thinking in new terms, to “go beyond the wall”. We also wish to extend our thanks to Carina Jahani, Uppsala University, for putting us in touch with the author and giving us valuable suggestions on our draft translation, as well as for writing the author introduction.